Implementation of Innovative Creative, Effective, and Fun Active Learning Using Games Sucker Ball - Al Hamidi, Febriyan (Universitas Negeri Semarang, 2016)
This study aims to determine the results of classroom learning using the method of learning models PAIKEM Sucker ball game compared to the class using lecture methods vary. The study design used in this study is the type of experimental research. Based on research results, the average post-test experimental class was 75.47, and the average grade control was 67.97. For results of test calculations with an average difference of post-test scores obtained thing = 1.403 while the table = 1.35 for α = 5% and dk = (32 +32-2) = 62 is obtained t (0.95) (62) = 1.35. Because t (0.95) (74) so, H0 is rejected, there are significant differences in the quality of learning between the experimental and the control groups. Based on the research results, it, there are differences in learning outcomes between the classes that use PAIKEM with learning outcomes using the lecture method.